Feasibility of Android-Based iSpring Suite Learning Media in Fiqh Subjects - Indah Miftahul Umam; Siti Sulaikho (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This research aims to know the properness of Ispringsuite based android system in Fiqh Material for The first grade in MTSN 14 Megaluh, Jombang. This research using Design-Based Research in Brog and Gall Approach. The research Instrument is formed as questionnaire validation of Material expert, linguistic expert, IT expert. On the other hand, there is also questionnaire validation for students respons. The assessment is conducted by classroom mean Score, Likert Scale. The result from a material expert is 81, 91% which claim as extremely proper, from the linguistic expert is 80,25% which named by very good. Besides, the score from IT experts is 70,61% which state as an appropriate category. And the score from the students is around 90%, Which state is highly proper. In conclusion, Ispring suite Learning Media based Android System in Fiqh Material is Proper to use.